Non-exhaust particulate matter emission from vehicles: A review - Guo Dongdong; Wei Hongyuan; Guo Yong; Wang Chuanqi; Yin Zenghui (E3S Web of Conferences, 2021)
According to the source, particulate matter produced during vehicle driving can be divided into exhaust emission and non-exhaust emission. Exhaust emission includes exhaust pipe emission and crankcase emission, while non-exhaust emission includes brake wear, tire wear, road wear and road dust. For a long time, it has been considered that the particulate matter pollution of motor vehicles mainly comes from exhaust emissions, and the control of particulate matter pollution in various countries is mainly concentrated in the tail gas. However, with the continuous tightening of emission standards, the emission of particulate matter has been reduced, but also makes the environmental pollution of non-exhaust particulate matter increasingly prominent. This paper summarizes the research on vehicle non-exhaust particulate matter emissions, aiming to emphasize the importance of non-exhaust particulate matter emissions and the necessity of legislation, so as to reduce their contribution to environmental particulate matter concentration.